2015
DOI: 10.7821/naer.2015.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risks in a Learning Management System: A case study in the Spanish National University of Distance Education (UNED)

Abstract: This article presents a research that examines the university students' risk perception when using a Learning Management System called "aLF" and implemented by the Spanish National University of Distance Education (UNED) for the development of its university distance studies. The development of comprehensive Learning Management Systems for teachinglearning distance practices in the European Higher Education Area (EHEA) is a challenge for universities all around Europe. For this reason, it is necessary to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…Parra- Meroño, 2017;Mondejar & Vargas, 2009;Vallejo, 2011); los ítems cuyas correlaciones ítem-total estuvieron por debajo del criterio de corte de 0,20 (Vázquez-Cano & Sevillano- García, 2015) son examinados y excluidos de la encuesta (Ramirez-Anormaliza et al, 2017).…”
Section: Marketingunclassified
“…Parra- Meroño, 2017;Mondejar & Vargas, 2009;Vallejo, 2011); los ítems cuyas correlaciones ítem-total estuvieron por debajo del criterio de corte de 0,20 (Vázquez-Cano & Sevillano- García, 2015) son examinados y excluidos de la encuesta (Ramirez-Anormaliza et al, 2017).…”
Section: Marketingunclassified
“…Both strategies aimed at identifying probable risks early and controlling them. Reference [36] examined the students' risk perception while using the aLF. The aLF is a LMS that was developed by Spanish National University of Distance Education (UNED), Vázquez-Cano and García found that risks are concentrated in two dimensions: "basic risks" and "own and beyond students' circumstances risks".…”
Section: Related Workmentioning
confidence: 99%
“…The fact that elearning needs to be managed and organised led to the development of Learner Management Systems (LMSs), which are used to automate the administration of the courses, record student use and student learning process. A strong LMS is expected to centralize and automate administration of e-learning activities, use self-service and selfguided services, assemble and deliver learning content rapidly and accurately, support mobility, personalize content and enable reuse of it (Vazquez-Cano & Garcia, 2015). An LMS offers various benefits to different stakeholders in the system.…”
Section: Introductionmentioning
confidence: 99%